2014
DOI: 10.1002/2013jb010581
|View full text |Cite
|
Sign up to set email alerts
|

Alaska Megathrust 2: Imaging the megathrust zone and Yakutat/Pacific plate interface in the Alaska subduction zone

Abstract: We image the slab underneath a 450 km long transect of the Alaska subduction zone to investigate (1) the geometry and velocity structure of the downgoing plate and their relationship to slab seismicity and (2) the interplate coupled zone where the great 1964 earthquake (M w 9.2) exhibited the largest amount of rupture. The joint teleseismic migration of two array data sets based on receiver functions (RFs) reveals a prominent, shallow-dipping low-velocity layer at~25-30 km depth in southern Alaska. Modeling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(187 citation statements)
references
References 72 publications
(166 reference statements)
17
164
1
Order By: Relevance
“…In particular, receiver functions have been useful in characterising the variations in the thickness and composition of continental crust (Zandt & Ammon, 1995), the geological processes active at subduction zones as the oceanic plate dives underneath a continent or another oceanic plate (e.g. Bostock et al, 2002;Abers et al, 2009;Kim et al, 2014), in continental transform settings (e.g. Ozacar & Zandt, 2009;Porter et al, 2011;Audet, 2015;Frederiksen et al, 2015) as well as the entanglement and geological transformation of crustal material in large collisional settings (e.g., Nábȇlek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, receiver functions have been useful in characterising the variations in the thickness and composition of continental crust (Zandt & Ammon, 1995), the geological processes active at subduction zones as the oceanic plate dives underneath a continent or another oceanic plate (e.g. Bostock et al, 2002;Abers et al, 2009;Kim et al, 2014), in continental transform settings (e.g. Ozacar & Zandt, 2009;Porter et al, 2011;Audet, 2015;Frederiksen et al, 2015) as well as the entanglement and geological transformation of crustal material in large collisional settings (e.g., Nábȇlek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The surface of the Nazca Ridge is imaged to be quite rugged, featuring many seamounts that penetrate the sediment cover (Hampel et al, 2004;Krabbenhoft et al, 2004). The thickness of the sediment layer is thin but variable, and sporadically missing along the margin (from 8 • S to 17 • S) (Krabbenhoft et al, 2004).…”
Section: Nazca Ridgementioning
confidence: 99%
“…The thickness of the sediment layer is thin but variable, and sporadically missing along the margin (from 8 • S to 17 • S) (Krabbenhoft et al, 2004). The total thickness of the sedimentary section atop the Nazca Ridge at a drill site 1237 (Fig.…”
Section: Nazca Ridgementioning
confidence: 99%
“…In contrast to the PWS segment, the Kenai and Kodiak segments involve the subduction of only Pacific plate rocks and contains less sediment above incoming plate mafic rocks. Higher density and greater westward age of the subducting oceanic lithosphere result in a steepening of the subduction angle (Plafker et al, 1994;von Huene et al, 1980;Eberhart-Phillips et al, 2006;Kim et al, 2014). The presumed subduction angle for the Kodiak Islands region is about 8 degrees and steepens to the north beneath mainland Alaska (Hayes et al, 2012).…”
Section: Tectonicsmentioning
confidence: 99%
“…Many studies have identified and characterized the PWS segment properties through various geophysical and geological investigations (Brocher et al, 1994;Eberhart-Phillips et al, 2006;Liberty et al, 2013;Kim et al, 2014). Similar literature exists for the Semidi segment that spans the region to the southwest of the Kodiak Islands (Johnson and Satake, 1994;Fournier and Freymueller, 2007;Shillington et al, 2015).…”
mentioning
confidence: 93%